The development and use of radiopaque markers for the assessment of gastric emptying in dogs : a thesis prepared in partial fulfilment of the requirements for the degree of Master of Veterinary Science at Massey University - Allan, Frazer James (Massey University, 1995)
Currently, there is no suitable technique that can be used by veterinarians in private practice to assess the rate of emptying of solids from the stomach of dogs. Radiographic studies using barium sulphate suspension are commonly employed by veterinarians to assess gastric emptying. However, these methods are qualitative and assess the gastric emptying of liquids not solids. Diseases which affect gastric emptying are more likely to affect the emptying of solids rather than liquids. The objective of this study was to develop a technique that the practising veterinarian could use to assess the rate of gastric emptying of solids in dogs. The study was divided into two parts, the development of radiopaque markers and the development of a method utilising these radiopaque markers that could be used in veterinary practice to assess the gastric emptying of solids. A 1.5 mm diameter (small) marker and a 5.0 mm diameter (large) marker were developed based on studies by other investigators. It was anticipated that the small marker would empty from the stomach with food and the large marker would empty with the onset of the migrating motility complex. Both markers were made from a compound containing high density polyethylene and barium sulphate. The gastric emptying of both sizes of marker was then assessed in 20 healthy, mixed breed dogs. Studies were performed on days one, six and nine of the investigation. After a 24 hour fast, thirty small and ten large markers were placed into a standard meal comprising of canned Prescription Diet® d/d. With the dogs restrained in ventrodorsal and left lateral recumbency, radiographs were taken hourly until all, or most of, the markers had emptied from the stomach. Percent gastric emptying of the markers versus time curves (GEvT curves) were then generated from this data. The time taken to reach the point of inflection on the GEvT curve (the lag phase), and the times taken to empty 25%, 50% and 75% of the markers (T25, T50 and T75 respectively) were calculated from the GEvT curves. The sex and age of the dogs and training the dogs to the radiographic procedure did not have a significant effect on the gastric emptying parameters. There was a weak but significant positive correlation between dog weight and the T50. There were no significant differences in the T25, T50 and T75 between the large and small markers. Contrary to their anticipated behaviour, the large markers left the stomach during the fed motility pattern. A larger, 7 mm diameter marker, may be required to mark the onset of the MMC in dogs. The mean GEvT curve of the small markers on day one (with 95% confidence intervals) was considered to represent the most appropriate gastric emptying reference curve for clinical use. The lag phase of the small markers on day one was 2.45 ± 2.04 hours, the T25 was 4. 85 ± 2.15 hours, the T50 was 6.05 ± 2.99 hours and the T75 was 8.32 ± 2.72 hours. If delayed gastric emptying is suspected, taking two or three sets of radiographs at regular intervals from 6-16 hours after feeding and comparing the results with the reference curve is probably the most appropriate method of assessing gastric emptying in a patient. Conversely, if excessively rapid gastric emptying is suspected, taking two or three sets of radiographs at regular intervals from 0-5 hours after feeding and comparing the results with the reference curve is most appropriate. In conclusion, radiopaque markers provide a simple quantitative method of evaluating the gastric emptying rate of dogs. However, the results of this study have not established that the gastric emptying of the small markers occurs at the same rate as the gastric emptying of food. In addition, the sensitivity and specificity of this diagnostic procedure still needs to be determined. These steps in the validation process are currently being carried out at the Department of Veterinary Clinical Sciences at Massey University.
Keywords: Gastrointestinal system motility; Dogs; Diseases; Diagnosis; Veterinary gastroenterology; Diagnostic imaging; Radiopharmaceuticals; Diagnostic use